TM mode analysis in a metamaterial based dielectric waveguide - Jin, Cheng (2014)
A TM mode analysis in a metamaterial based dielectric waveguide is proposed and introduced. Rigorously derived from Maxwell's equations, the dispersion properties are focussed on the fundamental properties of bound, surface and leaky modes of metamaterial based dielectric waveguide. Comparing with the conventional right handed material based waveguide, typical backward wave characteristic of volume and surface wave modes are found from the distribution of Poynting power to the transverse direction of waveguide.